IDENTIFIKASI PENGAWET DAN PEWARNA BERBAHAYA PADA BUMBU GILING YANG DIPERJUALBELIKAN DI PASAR DAYA MAKASSAR - Muliyati Tahir; Nardin Nardin; Juhra Nurmawati S (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
The aim of this study to find out if there are any Preservative and dye milled seasoning Regency using five samples with sampling techniques, namely purposive sampling conducted with qualitative tests and quantitative tests on Laboratorium Klinik GG Kota Makassar, Provinsi Sulawesi Selatan on 6 Juli 2016. . The results of laboratory tests on sample levels in salt with a qualitative test showed positive results in all samples and quantitative tests obtained sample seasoning content that in sample C the sample content was in accordance with SNI standards. In sample B and sample E approaching from the established SNI standard while in samples A and D are far below the SNI standard. Based on the results of the studymilled seasoning